Influence of pellet size on growth performance in nursery pigs and growth performance, nutrient digestibility, and stomach morphology in finishing pigs - Traylor, S.L.; Behnke, Keith C.; Sorrell, P.; Fairchild, Fred J.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pellet size (i.e., 3/32 in., 5/32 in., 5/16 in., and 1/2 in. diameter) had little effect on growth performance during the early stages (d 0 to 5) of the nursery phase. However, the 5/32 in. diameter pellets supported the best efficiencies of gain during the overall nursery (d °to 29) and finishing phases.
Keywords: Swine; Nursery pigs; Finishing pigs; Pellet size; Growth